English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i to the square root of 2, -i to the square root of 2

2007-01-29 17:33:32 · 1 answers · asked by roflroflrofl123 3 in Science & Mathematics Mathematics

1 answers

if an equation has a square root=a , you can divide it by (x-a)

so the equation is (x -i 2^0.5)(x -i2^0.5)

and knowing that (a-b) (a+b) = a^2+b^2

the equation is x^2 -2^0.5i^2 = x^2+2 since i^2 =-1

So x^2+2 =0

2007-01-29 17:47:58 · answer #1 · answered by maussy 7 · 0 0

fedest.com, questions and answers